BODY COMPOSITION IN PHYSIOLOGICALLY PROCESSING PREGNANCY IN WOMEN WITHOUT OBESITY OF THE YAROSLAV REGION - Матвеев, Игорь Михайлович; Троханова, Ольга Валентиновна; Щелыкалина, Светлана Павловна; Романова, Вера Сергеевна (Mother and Baby in Kuzbass, 2021)
The purpose of our study was to obtain ranges of basic parameters of body composition in physiologically occurring pregnancy in women without obesity at different gestation periods.To achieve this goal, a prospective cohort study of 195 women from 7 to 40 weeks of gestation living in the Yaroslavl region was conducted. All subjects underwent a standard clinical examination in accordance with the Order of the Ministry of health of the Russian Federation dated November 1, 2012. N 572N and bioimpedance analysis of body composition using the analyzer for evaluating the balance of water sectors of the body with the software ABC-01 «MEDAS». Normative data on the resistance of biological tissues were obtained, as well as the main parameters of body composition at different gestation periods were calculated. Dynamic observation during the entire pregnancy and analysis of the birth history were performed.The obtained data will allow us to analyze the peculiarities of adaptation of a woman's body to pregnancy, as well as to identify pathological changes in the body composition in the early stages of gestation, which can be predictors of the development of obstetric pathology in later pregnancy.
Keywords: pregnancy; body composition; bioimpedance analysis; total body fluid; body fat mass; electrical conductivity of biological tissues; extracellular fluid